Peran Media Digital dalam Meningkatkan Keterlibatan dan Partisipasi Publik: Transformasi Komunikasi di Era Informasi dan Sosial - Rika Aulia Maharani Srg; Usiono Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Digital media, especially social media, has become an important part of people's daily lives. Its presence has brought about major changes in the way society communicates, shifting from conventional methods to more modern and technology-based methods. Digital media makes communication faster, more efficient and easily accessible to all groups. In addition, this media offers people the opportunity to share information, interact and create social networks without geographic boundaries. However, despite the benefits, there are challenges such as misuse of information and lack of face-to-face interaction. This research examines how the role of digital media influences communication in everyday life, both positively and negatively. The results show that digital media has helped create more effective communication, although it still needs to be balanced with wise management to overcome its negative impacts.